ESTIMATING WATER QUALITY OF THE ARIAKE SEA IN JAPAN USING LANDSAT-TM DATA - Evaluation of SDD and SST- - Thian Yew Gan; Koichiro Ohgushi; Hiroyuki Araki (Lowland Technology International, 2000)
Using Lowtran 7's estimated Rayleigh scattered and aerosol scattered radiance, the radiance reflected at the sea surface (Lw(λ)) is derived from the measured radiance of Landsat-TM images taken over teh Ariake Sea. Then the Lw(λ) averaged from 4 x 4 windows of pixels contered at 33 sampling sites was regressed againts the observed Secchi disk depth (SDD) using linear regression algorithms. Result show that use of multi-date visible channels of Landsat-TM as the calibration data predicts more accurate and dependable SDD at the validation stage than use of single-date calibration data of Landsat-TM. This study confirms the feasibility of retrieving SDD (or turbidity/ suspended-sediments) from Landsat-TM data. Limited experiments in the modeling sea surface temperature (SST) show the potential of predicting SST from the thermal channel (6) og Landsate-TM data using a simple liniear regression.